Penerapan Model Pembelajaran Problem Based Learning (PBL) untuk Meningkatkan Pengetahuan Siswa pada Materi Keselamatan dan Kecelakaan Kerja (K3) di SMK Negeri 1 Dlanggu - Aura Khansa Balqist; Asrul Bahar; Niken Purwidiani; Mauren Gita Miranti (Journal on Education, 2023)
One of the problems in the learning process is that there are still many students who tend to be passive during learning activities because the teacher is still considered the main source of learning. The learning process will feel boring, the result is that many students are busy on their own, sleepy, joking with their friends, even playing gadgets. The objectives of this study, namely; (1) to know the implementation of syntax, (2) to know student activity, (3) to know student responses, and (4) to know the effect of problem-based learning on increasing student knowledge. The Problem Based Learning (PBL) learning model applies a Student Centered learning style or learning that focuses on students so that the teacher is only a facilitator. This research only focuses on increasing knowledge or cognitive, where the knowledge aspect is oriented towards developing thinking skills that include intellectual abilities ranging from remembering to solving problems. This research method is quantitative with experimental research type and research design in the form of control group pretest-posttest design. The data analysis technique uses the t test. The results of data analysis get an average difference between the pretest score of 65.71 and the posttest of 86.82 and are supported by hypothesis testing using the Independent t-test which gets a result of 0.035, where the significance is <0.05 which means H0 is rejected and Ha is accepted so it can be concluded that the problem-based learning model can increase student knowledge.